Contributo patristico alla questione 93 della Prima Pars della Summa Theologiae di san Tommaso d’Aquino - Rossi, Margherita Maria (Vox Patrum, 2025)
The present essay proposes an examination of q.93 of the Prima Pars of the Summa Theologiae of St. Thomas Aquinas - which he wrote primarily starting from the doctrine of St. Augustine - in which the theme of the human being created in the image and likeness of God is examined, with the Thomistic deepening of the specific theological lexicon involved. The resulting anthropological vision is affirmed in the famous prologue of the entire Prima Secundae that Aquinas sets up by profitably integrating the sources of Aristotle and John Damascene, the latter in turn indebted to the work of Nemesius of Emesa. The relevance of the introduction of the new Greek-patristic sources in the Middle Ages stands out not only in the passage from q.93 of the Prima Pars to the prologue of the Prima Secundae - as this essay intends to illustrate - but also in the making of the prologue itself.